The role of institutions in economic performance - Vitola, Alise; Senfelde, Maija (Business: Theory and Practice, 2015)
The purpose of the article is to survey the significant literature on the role of institutions – formal and informal constraints that affect investment in physical and human capital – in economic performance and propose a new, comprehensive definition and classification of institutions, as well as to develop a conceptual model to illustrate the interaction between institutions and socioeconomic development. The literature shows that institutions played an important role in facilitating technological progress and leading the world into the modern economic regime. Moreover, quantitative research proves that institutions significantly impact socioeconomic performance around the globe.